FMR1 expression in human granulosa cells increases with exon 1 CGG repeat length depending on ovarian reserve - Rehnitz, Julia; Alcoba, Diego Duarte; Dietrich, Jens Erik; Youness, Berthe; Hinderhofer, Katrin; Messmer, Birgitta; Freis, Alexander; Strowitzki, Thomas; Germeyer, Ariane (Reproductive biology and endocrinology, 2018)
Fragile-X-Mental-Retardation-1- (FMR1)-gene is supposed to be a key gene for ovarian reserve and folliculogenesis. It contains in its 5’-UTR a triplet-base-repeat (CGG), that varies between 26 and 34 in general population. CGG-repeat-lengths with 55-200 repeats (pre-mutation = PM) show instable heredity with a tendency to increase and are associated with premature-ovarian-insufficiency or failure (POI/POF) in about 20%. FMR1-mRNA-expression in leucocytes and granulosa cells (GCs) increases with CGG-repeat-length in PM-carriers, but variable FMR1-expression profiles were also described in women with POI without PM-FMR1 repeat-length. Additionally, associations between low numbers of retrieved oocytes and elevated FMR1-expression levels have been shown in GCs of females with mid-range PM-CGG-repeats without POI. Effects of FMR1-repeat-lengths-deviations (n < 26 or n > 34) below the PM range (n < 55) on ovarian reserve and response to ovarian stimulation remain controversial.